Respuesta :

Answer:

a. 2

b. 3

c. 3x^2+9x+15

d. 257

Step-by-step explanation:

[tex]f(x)=x^{2}+1 \\g(x)=3x+4 \\[/tex]

When a function is written like that the value in the parenthesis is what you use to replace the x inside the expression.

a. f(-1) means the value of function "f" when x = -1

[tex]f(-1)=(-1)^{2}+1=1+1=2[/tex]

b. "f" when x = -2 + "g" when x = -2

[tex]f(-2)+g(-2)=(-2)^{2}+1+3(-2)+4=3[/tex]

c. multiply for 3 each function

[tex]3f(x)+3g(x)=3(x^{2}+1)+3(3x+4)=3x^{2}+9x+15[/tex]

d. "g" when x = 4 then "f" when x = g(4)

[tex]g(4)=3(4)+4= 16\\f(g(4))=f(16)=16^{2}+1 = 257[/tex]